2016
DOI: 10.3389/fphar.2016.00122
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bep or Carboplatin Chemotherapy on Testicular Function and Sperm Nucleus of Subjects with Testicular Germ Cell Tumor

Abstract: Young males have testicular germ cells tumors (TGCT) as the most common malignancy and its incidence is increasing in several countries. Besides unilateral orchiectomy (UO), the treatment of TGCT may include surveillance, radiotherapy, or chemotherapy (CT), basing on tumor histology and stage of disease. It is well known that both radio and CT may have negative effects on testicular function, affecting spermatogenesis, and sex hormones. Many reports investigated these aspects in patients treated with bleomycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 31 publications
5
35
0
1
Order By: Relevance
“…Although there is an abundance of data reporting on the impact of BEP therapy, data reporting on the impact of carboplatin are sparse. Nevertheless, a recent study found that one cycle of carboplatin had no effect on fertility or sex hormones, suggesting that this regimen does not affect spermatogenesis .…”
Section: Testicular Cancer Treatment and Infertilitymentioning
confidence: 98%
See 1 more Smart Citation
“…Although there is an abundance of data reporting on the impact of BEP therapy, data reporting on the impact of carboplatin are sparse. Nevertheless, a recent study found that one cycle of carboplatin had no effect on fertility or sex hormones, suggesting that this regimen does not affect spermatogenesis .…”
Section: Testicular Cancer Treatment and Infertilitymentioning
confidence: 98%
“…© 2018 The Authors BJU International © 2018 BJU International one cycle of carboplatin had no effect on fertility or sex hormones, suggesting that this regimen does not affect spermatogenesis [47].…”
mentioning
confidence: 97%
“…The small sample size and bias, especially ascertainment bias, which is introduced in any cohort study, limit this study. Although it is known that carboplatin does not affect fertility compared to BEP (33), this study did not look at the fertility outcomes in these patients. Future studies should also incorporate long-term cardiovascular events in carboplatin-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…He was not referred for surgical sperm extraction before chemotherapy because of the low risk of gonadal toxicity from 1 carboplatin cycle. 3 At last follow-up, his testosterone was normal (18.7 nmol/L) ( Figure 4) without evidence of disease recurrence, and the couple was referred for microsurgical sperm retrieval followed by in vitro fertilization with intracytoplasmic sperm injection. 4 Extragonadal germ cell tumor treatment and prognosis depend on factors such as cancer type, tumor location, and tumor size.…”
Section: Hypertestosteronemia and Infertility From A Mediastinal Extrmentioning
confidence: 99%